When is it appropriate to be a whistleblower? the case of Mercy Medical Center - Castleberry, Stephen B.; Coleman, Joshua T. (London : NeilsonJournals Publishing, 2015)
Steve found evidence of an infraction of organizational policy when Joe, an employee and one of his best friends, used the organization's receiving services for personal use (the delivery of a case of wine). Such an infraction was seriously frowned upon at Mercy Medical Center, and employees were continually reminded of the correct policies and procedures. Upon further investigation, Steve learned that Joe had actually charged the organization for the wine and had done so on several previous occasions. Should Steve report his good friend and fellow employee for breaking organizational policy?
Originally Published InCastelberry, S. B., & Coleman, J. T. (2015). When is it appropriate to be a whistleblower? The case of Mercy Medical Center. Journal of Business Ethics Education, 12(1), 173-184. JBEE12-0CS4.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mercy Medical Center; Whistle blowing; Business ethics